2017
DOI: 10.1002/pds.4319
|View full text |Cite
|
Sign up to set email alerts
|

Thrombotic risk minimization for Diane‐35 and generics

Abstract: This descriptive analysis showed similar proportions of CPA/EE users examined with acne or other hyperandrogenic conditions, or with recent acne treatment, or concomitant dispensing of other HC in the Netherlands before and after the referral procedure. The key observation was a strong overall reduction of CPA/EE use in the Netherlands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…Social media appeared more reactive, showing more activity for the drug in question after a DHPC was published than before. Our finding that DHPCs related to drugs without a specialist indication were covered more often seems to be in line with earlier studies showing a high newspaper coverage of non-specialist drugs, such as cyproterone acetate/ ethinylestradiol (Diane-35) and rofecoxib [Vioxx (selective serotonin reuptake inhibitor)] [13,35]. With regard to social media, one might also expect more postings by laypeople on common non-specialist drugs because such drugs are more widely used.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Social media appeared more reactive, showing more activity for the drug in question after a DHPC was published than before. Our finding that DHPCs related to drugs without a specialist indication were covered more often seems to be in line with earlier studies showing a high newspaper coverage of non-specialist drugs, such as cyproterone acetate/ ethinylestradiol (Diane-35) and rofecoxib [Vioxx (selective serotonin reuptake inhibitor)] [13,35]. With regard to social media, one might also expect more postings by laypeople on common non-specialist drugs because such drugs are more widely used.…”
Section: Discussionsupporting
confidence: 90%
“…However, this media attention may also have contributed to an observed unintended decrease of use in adults [11]. While large changes in drug use have been reported for safety issues that were extensively covered by the media [13][14][15][16][17][18], systematic reviews suggested a more modest, if any, effect for a wide range of studied safety communications that generally may not have received much media attention [5,9,10]. It remains, however, largely unknown to what extent media in general pay attention to drug safety issues reviewed by regulatory authorities.…”
Section: Introductionmentioning
confidence: 99%
“…According to different studies, CPA should not be used only as a contraceptive. It can be prescribed in specific complaints like moderate to severe acne and hirsutism in women in reproductive age, but only if alternative treatments, such as topical therapy and systemic antibiotic treatment, have failed [4,8].…”
Section: Cyproterone Acetate (Cpa)mentioning
confidence: 99%